INCREASING MADRASAH STUDENTS' LEARNING INTEREST AND UTILIZATION OF NAGARI-BASED LIBRARY INFORMATION SERVICES: COMMUNITY STRATEGY - Yuliani, Tri (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2023)
The problem in this study is how to increase student's interest in learning after being given information services at MAN Sawahlunto. The purpose of this study was to increase students' interest in learning classes XII A and XII S at MAN Sawahlunto in a better direction through the implementation of information services. The research method used in this research is Action Research, where the author is the implementer of Information Services and the homeroom teacher of class XII A and XII S MAN Sawahlunto is an observer of information services provided to students who have a lack of interest in learning. The condition of students' interest in learning before being given action is that there are still many students who do not pay attention to the teacher who is giving subject matter, cheat, and daydream until they make noise during the teaching and learning process. In addition, students lack interest in learning. The results obtained in cycle I show that student interest in learning has not increased evenly because there are still students who have an interest in learning in the low and very low categories. In cycle II, students' interest in learning still did not increase evenly because there were still students who had an interest in learning in the low category. The results of cycle III research are very good compared to the previous cycle because, in this cycle, the average student interest in learning has increased, and there are no students in the low category who have an interest in learning. The increase in student interest in learning and the learning process can be seen in the attitude of students toward learning and their activeness in the classroom. because there has been an increase in student interest in learning, this research is only held three cycles.